(untitled) (Bangladesh Veterinarian, 2012)
Twelve one-month-old rats (Rattus norvegicus) were randomly divided into three groups of four. All groups were fed commercial diet, 20 g/rat for seven days. In addition, groups A and B were given home made probiotic (curd), commercial probiotic (Bio-Top®). Total serum cholesterol in A, B and C was 91.6 ± 3.6, 92.1 ± 1.2 mg, 122.3 ± 4.9 mg/dl, respectively. Triglyceride in A (47.5 ± 16.4 mg/dl), B (44.0 ± 5.0 mg/dl) and C (146.4 ± 25.4 mg/dl) differed significantly (P<0.01). High Density Lipoprotein (HDL) in A (79.2 ± 0.4 mg/dl), B (80.5 ± 0.9 mg/dl), C (73.7 ± 1.3 mg/dl) and Low Density Lipoprotein (LDL) in A (2.8 ± 0.2 mg/dl), B (2.9 ± 0.3 mg/dl), C (19.3 ± 5.9 mg/dl) also differed significantly (P<0.01). Serum aspartate transaminase (AST) in A (112.8 ± 1.4 U/L), B (110.5 ± 6.0 U/L), C (134.2 ± 3.5 U/L), Serum alanine transaminase (ALT) in A (31.7 ± 2.3 U/L), B (27.3 ± 2.2 U/L), C (40.7 ± 5.7 U/L) differed significantly (P<0.01). Creatinine in A (0.8 ± 0.1 mg/dl), B (0.7 ± 0.1 mg/dl), C (0.7 ± 0.1 mg/dl) did not differ significantly. It is suggested that the probiotics altered blood chemistry in the rats. DOI: http://dx.doi.org/10.3329/bvet.v28i2.10685 Bangl. vet. 2011. Vol. 28, No. 2, 70 74